Ethanol Fermentation Potency of Wild Yeast Which Isolated From Soil Drive Nutrient (Sdn) Plantation System - Anton Muhibuddin; Indira Rizqita Ivanesthi; Sri Nurhatika; Tjuk Eko Hari Basuki (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2017)
Yeast which has a fermentative type can ferment alcohol, which break down the sugars into alcohol, lactic acid and gas. This yeast’s type is needed in biofertilizer process production. The purpose of this study was to observed the potential in ethanol production of the soil wild yeast that isolated from Jember-East Java, and determine the concentration of sugar product as well as the best time of ethanol fermentation. Our previously observation have found 113 yeast species. Then we select them based on fermentative ability and found five best species. These five species then has determined it’s sugar product as well as the best time of ethanol fermentation and choose two best. We have counted the level of ethanol production using glucose medium of 10%, 15% and 20% of these two best species. The results showed that Candida sp. 1 (species number-1) and Candida sp. 3 (species number-3) has a better potential to produce ethanol. The highest ethanol content was produced by Candida sp. 1 (56%) while by Candida sp. 3 (70%). While the optimum time for the ethanol fermentation process Candida sp. 1 and Candida sp. 3 is 24 hours.